Effect of metabolic syndrome on incidence of oral potentially malignant disorder: a prospective cohort study in Taiwan - Yen-Po Yeh; Tony Hsiu-Hsi Chen; Li-Sheng Chen; Amy Ming-Fang Yen; Pallop Siewchaisakul; Sen-Te Wang; Szu-Min Peng; Pongdech Sarakarn (BMJ Open)
Objectives We aimed to assess the effect of metabolic syndrome (MetS) on incident oral potentially malignant disorder (OPMD).Design We conducted a prospective cohort study of the Changhua community-based integrated screening (CHCIS) programme and nationwide oral cancer screening programme during the period between 2005 and 2014.Setting CHCIS, Taiwan.Participants We enrolled 17 590 participants aged 30 years and older.Main outcomes and measures We assessed the impact of MetS on the outcome measured by incident OPMD.Results The incidences of OPMD among subjects with and without MetS were 7.68 ‰ and 5.38 ‰, respectively. After adjusting for confounders, subjects with MetS exhibited a statistically greater risk of developing OPMD compared with those who were free of MetS by 33% (adjusted rate ratio, aRR=1.33, 95% CI 1.14 to 1.55). Individual components of MetS still remained significant, including central obesity (aRR=1.22, 95% CI 1.04 to 1.44), hypertriglyceridaemia (aRR=1.26, 95% CI 1.07 to 1.49) and hyperglycaemia (aRR=1.20, 95% CI 1.02 to 1.41). Central obesity and hypertriglyceridaemia were also statistically associated with a subtype of OPMD, namely, leukoplakia.Conclusion The temporal influence of MetS on the risk of incident OPMD was noted in our prospective cohort study. Therefore, promoting an MetS prevention and control programme might reduce the occurrence of OPMD and oral cancer.